08.18 Anti-citrullinated protein antibodies: a marker of cardiovascular disease and mortality in patients without rheumatoid arthritis. (1st March 2017) - Hermans, Maaike PJ; Volkov, Mikhail; Velden, Daniel van der; Cabezas, José M Montero; Huizinga, Tom WJ; Kuiper, Johan; Toes, Rene EM; Schalij, Martin J; Jukema, J Wouter; van der Woude, Diane
Abstract : Background: Patients with rheumatoid arthritis (RA) have a high risk of cardiovascular mortality, which is further increased in presence of anti–citrullinated protein antibodies (ACPA). Recently, ACPA were unexpectedly detected in a cohort of patients with coronary artery disease (CAD) in the absence of RA. However, it is unknown if ACPA are consistently present in different cohorts of CAD patients, and if ACPA presence affects the course of cardiovascular disease in these patients. The purpose of this study was to assess the relationship between ACPA and long-term outcomes (including mortality) in patients with ST-elevation myocardial infarction (STEMI) in the absence of RA. Materials and methods: Patients with from the MISSION! Intervention Study were included (n=275). The cohort consists of patients with STEMI, who subsequently underwent a percutaneous coronary intervention. Patients with RA were excluded. ACPA positivity was determined using a commercially available ELISA system (Quanta Lite CCP3.1 IgG/IgA). The association between ACPA (anti-CCP3) status at baseline and outcomes, such as re-infarction and death, was investigated during a 10 year follow-up. Results: In total, 29 (11%) of 275 included patients were ACPA-positive, substantiating the previous description of ACPA in CAD patients. Increased cumulative cardiac mortality was observed in ACPA-positive patients in comparison with ACPA-negative patients. Moreover, after correction for additional associated factors (such as age, gender, body mass index, presence of diabetes, etc.), ACPA-positivity was still associated with increased long-term mortality (HR 3.1 [CI 1.4–7.1] p=0.01] and the long-term combined endpoint of re-infarction and death (HR 2.4 [1.2–4.6] p=0.01). Conclusions: Among STEMI patients without RA, the presence of ACPA is independently associated with increased long-term mortality and the combined endpoint of re-infarction and death. We suggest that ACPA, previously solely linked to RA development and severity, may also play a role as an additional risk factor in cardiovascular disease. The hypothesis that ACPA might act as an independent pro-atherogenic factor in patients with and without RA, has to be investigated in subsequent studies.